What Affects Facing Direction in Human Facial Profile Drawing? A Meta-Analytic Inquiry. (December 2014) - Tosun, Sümeyra; Vaid, Jyotsna
Two meta-analyses were conducted to examine two potential sources of spatial orientation biases in human profile drawings by brain-intact individuals. The first examined profile facing direction as function of hand used to draw. The second examined profile facing direction in relation to directional scanning biases related to reading/writing habits. Results of the first meta-analysis, based on 27 study samples with 4171 participants, showed that leftward facing of profiles (from the viewer's perspective) was significantly associated with using the right hand to draw. The reading/writing direction meta-analysis, based on 10 study samples with 1552 participants, suggested a modest relationship between leftward profile facing and primary use of a left-to-right reading/writing direction. These findings suggest that biomechanical and cultural factors jointly influence hand movement preferences and in turn the direction of facing of human profile drawings.